Emerging roles of lipid and metabolic sensing in the neuroendocrine control of body weight and reproduction - Rodríguez-Vázquez, Elvira; Aranda-Torrecillas, Álvaro; López-Sancho, María; Castellano, Juan M.; Tena-Sempere, Manuel (Frontiers in Endocrinology, 2024)
The hypothalamus lies at the intersection of brain and hormonal mechanisms governing essential bodily functions, including metabolic/body weight homeostasis and reproduction. While metabolism and fertility are precisely regulated by independent neuroendocrine axes, these are tightly connected, as reflection of the bidirectional interplay between the energy status of the organisms and their capacity to reproduce; a connection with important pathophysiological implications in disorders affecting these two crucial systems. Beyond the well-characterized roles of key hormones (e.g., leptin, insulin, ghrelin) and neuropeptides (e.g., melanocortins, kisspeptins) in the integral control of metabolism and reproduction, mounting evidence has pointed out a relevant function of cell energy sensors and lipid sensing mechanisms in the hypothalamic control of metabolism, with prominent roles also for metabolic sensors, such as mTOR, AMPK and SIRT1, in the nutritional regulation of key aspects of reproduction, such as pubertal maturation. We provide herein a synoptic overview of these novel regulatory pathways, with a particular focus on their putative function in the metabolic control of puberty, and delineate new avenues for further exploration of the intricate mechanisms whereby metabolism and reproduction are tightly connected.